STUDY OF ANTIVIRAL ACTIVITY OF SOME HYDRAZONE PINOSTROBIN DERIVATIVES - G. K. Mukusheva (Farmaciâ i Farmakologiâ (Pâtigorsk), 2015)
New derivatives on the basis of hydrazone pinostrobin molecule were synthesized. Significant antiviral activity of received samples of new hydrazone pinstrobin derivatives was identified.